The Effectiveness Of Gamification in Enhancing Student Engagement In Science Learning - Gigih Abdi Wijaya; Ahmad Zulfan Tantowi; Elsavira Nurizzah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research investigates the effectiveness of gamification strategies in enhancing student engagement and motivation in science education. The study introduces gamified learning activities, such as point systems, leaderboards, and digital badges, into the science curriculum. Through a series of surveys and classroom observations, the research finds that gamification significantly increases student participation, interest, and overall achievement in science subjects. The paper discusses the benefits of incorporating game-based elements into science teaching and provides recommendations for educators looking to implement gamification in their classrooms.